The Importance of Digital Transformation in Maritime Law Enforcement at Sea - Irma Rachmawati Maruf (SEAN Institute, 2024)
Maritime law enforcement is an important aspect in maintaining security and sustainability of maritime activities at sea. However, complex challenges such as territorial expansion, increasing illegal activities, and cross-border presence demand the adoption of new technologies in maritime law enforcement. This research examines the importance of digital transformation as an effective solution in increasing the efficiency and effectiveness of maritime law enforcement at sea. This research uses a normative legal approach based on applicable regulations. The research results show that digital transformation has a positive impact on maritime law enforcement at sea. Information system integration enables data exchange between law enforcement agencies, strengthens cross-agency collaboration, and increases operational efficiency. The use of digital technology also makes it possible to detect and deal with illegal activities at sea, such as illegal fishing and smuggling, more effectively. In addition, digital transformation provides a solid foundation for holistic and sustainable maritime policymaking, supporting more effective and sustainable management of marine resources in the long term.